2014
DOI: 10.1016/j.paid.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation, negative affect, and aggression: A moderated, multiple mediator analysis

Abstract: Research on violence has highlighted the role of trait negative affect in reactive aggressive behavior. Emotion dysregulation is a multidimensional construct reflecting maladaptive ways in which a person experiences and responds to emotional states, and has also been empirically linked to aggression. This study sought to test the hypothesis that multiple facets of emotion dysregulation would mediate the relationship between negative affect and physical aggression in a nonclinical sample. An additional aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 29 publications
(32 reference statements)
8
61
1
5
Order By: Relevance
“…Support for a role for emotion dysregulation in the acquired capability has, to some extent, been driven by prior research demonstrating robust associations between emotion dysregulation and such behaviors. Indeed, converging evidence has suggested that individuals who struggle with tolerating and regulating intense and labile emotions gain the capability for suicide by instigating self-destructive emotion regulation behaviors [17] such as NSSI [24,25], aggressive behavior [26], and intravenous drug use [27].…”
Section: Acquired Capabilitymentioning
confidence: 99%
“…Support for a role for emotion dysregulation in the acquired capability has, to some extent, been driven by prior research demonstrating robust associations between emotion dysregulation and such behaviors. Indeed, converging evidence has suggested that individuals who struggle with tolerating and regulating intense and labile emotions gain the capability for suicide by instigating self-destructive emotion regulation behaviors [17] such as NSSI [24,25], aggressive behavior [26], and intravenous drug use [27].…”
Section: Acquired Capabilitymentioning
confidence: 99%
“…Calkins (1994) detailed a theoretical framework in which behavioral traits influence emotion regulation and argued that positive or negative affect act as sources of individual variation in emotion regulation (23). More recently, empirical investigations have investigated emotion regulation as a mediator between negative affect and aggression (24). Kim-Spoon, Cicchetti, and Rogosch (2013) found the effects of emotion negativity on internalizing symptoms were completely mediated through emotion regulation (25).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, McLaughlin et al (44) believed that individuals inevitably resort to undesirable behaviors to make themselves relieved when they cannot make use of problem-oriented and adaptive strategies to deal with their obsessive tendencies. Such behaviors can include smoking and substance abuse (15,45,46), inclination to suicidal thoughts (47), as well as aggressive behaviors (48). analysis of some influential psycho determinants on cravings towards smoking in adolescents.…”
Section: Discussionmentioning
confidence: 99%